Стендовые испытания полноразмерных теплообменников танка БМ "Оплот" - Колбасов, А. Н. (НТУ "ХПИ", 2009)
The main approaches to bench tests in big wind tunnel of heat exchangers for cooling system of “Oplot” MB tank are presented. It let to test the industrially manufactured units and estimate their aerodynamic, hydraulic and thermal characteristics.
Keywords: танки; эжекционная система охлаждения; теплообменники; охлаждающая жидкость; отвод тепла; радиатор; танк БМ "Оплот"; стендовые испытания